Strain improvement of Lentzea sp. 7887 for higher yield per unit volume on hydroxylation of cyclosporine derivative FR901459. Issue 7 (3rd July 2017) - Yabutani, Tetsuya; Tsujimoto, Mami; Ohira, Shunsuke; Shimizu, Shiho; Nakano, Hideo
Abstract: A Gram-positive bacterium Lentzea sp. 7887 hydroxylates a cyclosporine derivative FR901459 into AS1837812 (9-hydroxide), which is an important intermediate of candidate drugs that target the hepatitis C virus. We screened a UV-induced mutant, named M-1, which showed about 1.2-fold higher conversion yields, 2-fold higher substrate concentrations (3.69 mM), and 2.5-fold higher yield per unit volume than the wild-type strain.